LEGAL ANALYSIS OF DIVORCE DUE TO EARLY MARRIAGE - Aryanti Aryanti; Efridani Lubis; Rohmad Adi Yulianto (Jurnal Hukum Jurisdictie, 2023)
The study of Juridical Analysis of Divorce Due to Early Marriage aims to determine the regulation of early marriage in positive law in Indonesia and to determine dispute resolution (divorce) due to early marriage. This study uses a normative juridical approach. The research method used in this research is descriptive analytical method, which is a research method by processing data, analyzing, researching and interpreting as well as making conclusions and providing suggestions which are then arranged in a systematic discussion so that the problem can be understood. The type of research used is normative law research. The results show that families experiencing economic difficulties will tend to marry off their children at a young age, this marriage is expected to be a solution to the economic difficulties experienced by families, marriage is expected to reduce the family's economic burden. Another influence is due to the low level of education that encourages them to get married quickly. Because they do not understand how marriage really is, the occurrence of pregnancy out of wedlock, because children have relationships that violate the norms forcing them to have early marriages in order to clarify the children conceived by this marriage force them to marry. There are still many women in Indonesia who marry underage for various reasons such as customs, economy, and other things that are not desirable. In fact, according to Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, it is stated that marriage is only permitted if the man and woman are 19 years old.